2001
DOI: 10.1046/j.1440-1754.2001.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of cardiac functions and left ventricular mass in children with malnutrition

Abstract: We demonstrated that LV Mass and cardiac output were reduced in proportion to decrease in body size in patients with PEM, and LV systolic and diastolic functions were preserved in atrophic hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
45
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 12 publications
12
45
0
1
Order By: Relevance
“…This comes in agreement with Ocal et al (2001) who reported that the diastolic function indices were not significantly affected in malnourished patients. Fioretto et al (2002) also reported that there is a geometric alteration of the left ventricle with preserved ventricular compliance and distensibility despite increased passive myocardial stiffness.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This comes in agreement with Ocal et al (2001) who reported that the diastolic function indices were not significantly affected in malnourished patients. Fioretto et al (2002) also reported that there is a geometric alteration of the left ventricle with preserved ventricular compliance and distensibility despite increased passive myocardial stiffness.…”
Section: Discussionsupporting
confidence: 93%
“…However, some patients showed borderline systolic function. This is in agreement with Ocal et al (2001). Similarly, Kothari et al (1992) did not find any evidence of systolic dysfunction in their patients, except in those with extremely severe PEM.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Effects of protein supply in pregnancy on left ventricular function have been described in rats (8). Similarly, infants and children suffering from protein-energy malnutrition have been shown to have reduced left ventricular mass (LVM) and function (9)(10)(11) proportional to body surface (10). In animal models, early life overnutrition has been associated with left ventricular hypertrophy (12).…”
mentioning
confidence: 99%